Enterobius vermicularis in children at daycare centers - Voigt, João Victor Dória; dos Anjos Ferreira Andrade , Rebecca; Martins Freixo , Danielle; Toscano Nalim , Giovanna; de Jesus dos Santos , Cyntia; Lisboa Correa , Laís; Terumi Nakashima, Flávia; Antunes da Silva , Ingrid; Monteiro Fonseca , Ana Beatriz; da Silva Barbosa , Alynne; et al. (Journal of Health & Biological Sciences, 2025)
Objective: this study aimed to evaluate the frequency of enterobiasis in children attending daycare centers in Niterói, RJ, Brazil, using different parasitological techniques, and correlating its frequency with socioeconomic factors and clinical manifestations. Methods: children from three community daycare centers were asked to fill out a questionnaire and collect perianal region material, using the Graham’s technique , and total feces, to be processed using the techniques of Faust et al., Ritchie modified, and fine-mesh screening. Results: Enterobius vermicularis was detected, exclusively by Graham’s technique , in 12% (11/92) of the children. The age of four to six years was a risk factor for acquiring enterobiasis (OR = 1.256). There were no associations between positivity for E. vermicularis and family income, number of children in the house, or the parent’s education level, among other variables. The use of two slides for the Graham’s technique showed substantial/excellent agreement, which indicates that this is an appropriate strategy for diagnosing enterobiasis, thus resulting in lower costs and less discomfort for children and their guardians. Conclusion: E. vermicularis was the most common parasite among children in Niterói, which indicates the importance of including the Graham’s technique in studies on the prevalence of intestinal parasites.